2012
DOI: 10.1186/2008-2231-20-12
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of the effect of intravenous paracetamol on inflammatory biomarkers and outcome in febrile critically ill adults

Abstract: Background and the purpose of the studyThe febrile reaction is a complex response involving immunologic and other physiologic systems. Antipyretics are commonly used in critically ill patients with fever. We investigated the inflammatory responses following application of antipyretic therapy in febrile critically ill patients with Systemic Inflammatory Response Syndrome (SIRS).Patients and methodsIn a prospective, randomized controlled study, critically ill patients with fever (T ≥ 38.3°C), SIRS diagnosed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…In the second study, 10 critically ill patients were administered 650 mg paracetamol intravenously every 6 h for 10 days; they were compared with 10 patients not administered any antipyretic unless core temperature reached 40°C. Circulating concentrations of interleukin 6 were significantly decreased from baseline in the paracetamol group but not in the control group, which was in agreement with our previous observations . However, two other prospective studies found that aggressive antipyretic treatment was not of benefit for critically ill patients with sepsis .…”
Section: Discussionsupporting
confidence: 92%
“…In the second study, 10 critically ill patients were administered 650 mg paracetamol intravenously every 6 h for 10 days; they were compared with 10 patients not administered any antipyretic unless core temperature reached 40°C. Circulating concentrations of interleukin 6 were significantly decreased from baseline in the paracetamol group but not in the control group, which was in agreement with our previous observations . However, two other prospective studies found that aggressive antipyretic treatment was not of benefit for critically ill patients with sepsis .…”
Section: Discussionsupporting
confidence: 92%
“…Although, management of patients in ICU is somehow complicated and dependent of the status of each patient [24], it was decided to use an established protocol as a base amount for moderate dose of magnesium that was safe over the years in ICU [25]. Two fold of that dose has been assumed as high dose of magnesium for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Data from critically ill patients in general are available. We reviewed the literature and identified 12 RCTs (1785 patients) that examined the effect of fever control in the critically ill population, excluding neurological indication for temperature control [160][161][162][163][164][165][166][167][168][169][170][171]; active temperature management (pharmacologic or non-pharmacologic) did not reduce the risk of death (RR 1.03, 95% CI 0.81-1.31), ICU length of stay (MD − 0.07 days, 95% CI − 0.70-0.56), but it was effective in reducing body temperature (MD − 0.36 °C, 95% CI − 0.42 lower to − 0.29). Given the safety of acetaminophen and lack of harm in the body of evidence, increasing patient comfort through fever management maybe important.…”
Section: Rationalementioning
confidence: 99%